Effect of hydrotherapy on sleep deficiency among older people in integrated community health services in Pandak I Bantul - Warseno Agus; Sukmawati Anastasia Suci (Sciendo, 2019)
Relaxation technique is a nonpharmacological treatment applied to increase sleep efficiency and the quality of sleep. Hydrotherapy is one of the relaxation techniques and uses warm water to decrease stress and muscle stiffness, as well as to warm the body. The incidence of sleep deficiency among older people in Integrated Community Health Services, Pandak I Bantul, has slightly increased year by year. This research aims to evaluate the effect of hydrotherapy on sleep deprivation among older people.